Compositional dependence of structures of NiTi martensite from first principles. (15th August 2015) - Mizuno, Masataka; Araki, Hideki; Shirai, Yasuharu
Graphical abstract: Abstract: We investigate the energetics and structures of martensitic phases in NiTi and the effects of chemical composition using first-principles calculations. We calculate the accurate energy landscape for the transformation from the B19 to BCO phases, which reveals that there is no energy barrier and no intermediate phase between the B19 and BCO phases. A local minimum corresponding to the B19′ phase does not appear in the stoichiometric composition. In the Ni-rich composition, the BCO phase rapidly becomes more unstable than the B19 phase with increasing Ni composition. As a result, an energy minimum corresponding to the B19′ phase appears in the Ni-rich composition. The main reason for these results is that the stacking manner of the bilayers in the B19 phase is stabilized by the Ni antisite atoms. Although a decreasing trend of the monoclinic angle of the B19′ phase with increasing Ni composition is observed in both the calculated and experimental structures, the calculated monoclinic angle of the B19′ phase is larger than the experimental value. The calculated formation energy of a Ni–Ti antisite pair in the B2 phase shows a negative value of energy, which indicates that Ni–Ti antisite pairs are introduced even in the stoichiometric B2 phase. These results suggest that the difference in the monoclinic angle between calculated and experimental results is partly explained by the decrease in the monoclinic angle by Ni and Ti antisite atoms introduced in the B2 phase.